Efficacy of Acupuncture Treatment of Migraine Delivered by Senior or Junior Acupuncturists: Study Protocol for a Randomized Controlled Trial - Zhou, Jun; Jiang, Nan-nan; Fang, Yu; Zhang, Xin-yue; Cheng, Shi-rui; Li, Xin-ling; Hu, Sheng-jie; Sun, Rui-rui; Zheng, Hua-bin; Huang, Xiao-peng; Zeng, Fang; Liang, Fan-rong; et al. (Frontiers in Neurology, 2022)
Introduction: Acupuncture is an efficacious and safe treatment choice for migraine prevention. Results from clinical trials have shown that non-specific effects play an important role in acupuncture’s efficacy. To date, however, there is no evidence available quantitatively evaluating the effect of non-specific effects, such as patients’ expectations and beliefs for acupuncturists, on acupuncture efficacy, necessitating further exploration. Methods: A total of 156 patients with migraine without aura (MwoA) will be randomized to either junior or senior acupuncturist group, at a ratio of 1:1. The study will last 24 weeks, for each patient, comprising baseline, treatment and follow-up phases lasting 4, 8 and 12 weeks, respectively. All patients will undergo 12 sections of acupuncture treatment delivered by either a junior or senior acupuncturist following the same acupuncture prescription and manipulation. The primary outcomes will be changes in the number of migraine days, and frequency of attacks per 4 weeks cycle, relative to the baseline. Secondary outcomes will include severity of headache pain, quality of life, anxiety/depression levels, and use of non-steroidal anti-inflammatory drugs (NSAIDs) per 4 weeks cycle, compared to the baseline, as well as adverse events and rate of positive response to treatment. Prior to randomization of patients into junior or senior acupuncturist groups, the Acupuncture Expectations Evaluation Scale (AES) will be used to evaluate their expectations and belief with regards to acupuncture efficacy delivered by senior or junior acupuncturists. Discussion: Results from this clinical randomized controlled trial will help to quantitatively evaluate the extent of the effect of acupuncture treatment delivered by a senior or junior acupuncturist (high relative to low expectations) in migraine patients. Ethics and dissemination: This trial has been approved by the Institutional Review Boards and Ethics Committees of Hospital of Chengdu University of Traditional Chinese Medicine (Approval No. 2020KL-058). Trial registration number: ChiCTR2100042963